The VARying effect of foreign shocks in Central and Eastern Europe - Rebeca Jiménez-Rodriguez; Amalia Morales-Zumaquero; Balázs Égert (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper investigates the impact of international shocks - interest rate, commodity price and industrial production shocks - on key macroeconomic variables in ten Central and Eastern European (CEE) countries by using near-VAR models and monthly data from the early 1990s to 2009. In contrast to previous work, the empirical analysis takes explicit account of the possibility of (multiple) structural breaks in the underlying time series. We establish strong evidence of structural breaks, particularly along the years 2007 and 2008, suggesting the very relevant impact of the recent global crisis on CEE economies. Moreover, our results suggest that the way how countries react to world commodity price shocks is related to the underlying economic structure and the credibility of the monetary policy. We also find that some countries like Slovakia and Slovenia - already euro area members - react stronger to foreign industrial production shocks than other countries and that the responses to such shocks are strongly correlated for selected CEE countries. Nevertheless, our results also shed light on substantial differences in responses to foreign interest rate shocks that originate from the US or the euro area.
Keywords: E43; E50; E52; C22; O52; 330; monetary policy; foreign shocks; multiple structural breaks; near-VAR model; CEE economies; Schock; Zins; International; Weltkonjunktur; Makroökonomischer Einfluss; VAR-Modell; Schätzung; Ostmitteleuropa